2016
DOI: 10.1038/srep28998
|View full text |Cite
|
Sign up to set email alerts
|

The RNA binding protein HuR determines the differential translation of autism-associated FoxP subfamily members in the developing neocortex

Abstract: Forkhead-box domain (Fox) containing family members are known to play a role in neocorticogenesis and have also been associated with disorders on the autism spectrum. Here we show that a single RNA-binding protein, Hu antigen R (HuR), dictates translation specificity of bound mRNAs and is sufficient to define distinct Foxp-characterized subpopulations of neocortical projection neurons. Furthermore, distinct phosphorylation states of HuR differentially regulate translation of Foxp mRNAs in vitro. This demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 44 publications
5
41
0
Order By: Relevance
“…Computational processing might have been facilitated by some of the changes presented here, at least in some of the circuits that have expanded in our lineage (Mars et al 2018), since subtle maturational differences early in development(Dubois et al 2016) may have had a considerable impact on the phenotype. In this context, it is worth mentioning that in our dataset, several genes carrying HHMCs and associated with basal ganglia functions (critical for language and cognition) stand out, like SLITRK1(Abelson et al 2005) and NOVA1(Jelen et al 2010;Konopka et al 2012;Alsiö et al 2013;Zhou et al 2015;Popovitchenko et al 2016) (Supplementary Information 4). Finally, in the broader context of cognition, we find an enrichment of HHMCs in genes associated to "Alzheimer's disease (cognitive decline)" and "Cognitive decline(age-related)", with seven associated genes (COX7B2, BCAS3, DMXL1, LIPC, PLEKHG1, TTLL2 and VIT).…”
mentioning
confidence: 97%
“…Computational processing might have been facilitated by some of the changes presented here, at least in some of the circuits that have expanded in our lineage (Mars et al 2018), since subtle maturational differences early in development(Dubois et al 2016) may have had a considerable impact on the phenotype. In this context, it is worth mentioning that in our dataset, several genes carrying HHMCs and associated with basal ganglia functions (critical for language and cognition) stand out, like SLITRK1(Abelson et al 2005) and NOVA1(Jelen et al 2010;Konopka et al 2012;Alsiö et al 2013;Zhou et al 2015;Popovitchenko et al 2016) (Supplementary Information 4). Finally, in the broader context of cognition, we find an enrichment of HHMCs in genes associated to "Alzheimer's disease (cognitive decline)" and "Cognitive decline(age-related)", with seven associated genes (COX7B2, BCAS3, DMXL1, LIPC, PLEKHG1, TTLL2 and VIT).…”
mentioning
confidence: 97%
“…Developmental titration of FOXP1 levels can be regulated through numerous mechanisms. There is evidence that this is accomplished, in part, by post-transcriptional regulation of FOXP1 mRNA through critical cis regulatory elements (CREs) (Huelga et al, 2012;Jangi & Sharp, 2014;Liu et al, 2014) and microRNAs (miRNAs) in UTRs of the gene (Otaegi, Pollock, Hong, & Sun, 2011;Popovitchenko et al, 2016). Bioinformatic analysis revealed that the variants observed were near the binding sites of mRNA-486-5p (mi-croRNA.org).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism underlying the effects of suramin in ASD is unclear. HuR regulated the translation of mRNA transcribed from autism‐associated genes, Foxp1 and Foxp2 . Suramin may have improved ASD by inhibiting HuR‐ Foxp1 and/or HuR‐ Foxp2 binding.…”
Section: Discussionmentioning
confidence: 99%